2006
DOI: 10.1097/00129689-200608000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Periampullary Duodenal Diverticula at Endoscopic Retrograde Cholangiopancreatography: A Proposed Classification of Periampullary Duodenal Diverticula

Abstract: PDD are common, especially in older patients, and do not significantly increase the difficulty of deep cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 18 publications
12
109
0
12
Order By: Relevance
“…Previous studies showed a high prevalence of JAD (1.83% to 32.8%). 1,2,[6][7][8][9][10][11][12][13][14] In our study, 225 patients were diagnosis with JAD after the use of ERCP. We report a prevalence of 4.5% that is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed a high prevalence of JAD (1.83% to 32.8%). 1,2,[6][7][8][9][10][11][12][13][14] In our study, 225 patients were diagnosis with JAD after the use of ERCP. We report a prevalence of 4.5% that is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Periampullary diverticula were classified as type I, II, or III according to the position of the major papilla from the endoscopic view (12). In type I, the major papilla was located inside of the diverticulum; in type II, the major papilla was located in the margin of the diverticulum; and in type III, the major papilla was located outside of the diverticulum.…”
Section: Assessment Of Risk Factors For Cbd Stone Recurrencementioning
confidence: 99%
“…5,13 Duodenal diverticula are rare below age 40 years and has a tendency to increase with age. [5][6][7][8][9]11 They intraluminal or extraluminal. They typically occur in the periampullary region, along the medial aspect of the second and third part of the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Diverticula usually found in people above 40 and has a tendency to increase with age. [5][6][7][8][9] PAD occurred in up to 65% of elderly patients in some studies. 10 Diverticula occur at locus minoris in the duodenal wall such as the site of entry of the common bile duct, pancreatic duct and perivascular connective tissue sheath.…”
Section: Introductionmentioning
confidence: 99%